2022
DOI: 10.1111/cas.15393
|View full text |Cite
|
Sign up to set email alerts
|

DDX55 promotes hepatocellular carcinoma progression by interacting with BRD4 and participating in exosome‐mediated cell‐cell communication

Abstract: The involvement of DEAD‐box helicase 55 (DDX55) in oncogenesis has been suggested, but its biological role in hepatocellular carcinoma (HCC) remains unknown. The present study verified the upregulation of DDX55 in HCC tissues compared with non‐tumor controls. DDX55 displayed the highest prognostic values among the DEAD‐box protein family for recurrence‐free survival and overall survival of HCC patients. In addition, the effects of DDX55 in the promotion of HCC cell proliferation, migration, and invasion were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
(173 reference statements)
0
6
0
Order By: Relevance
“…Two recent studies reported that the human Spb4 homolog DDX55 is strongly upregulated in various lung cancers and hepatocellular carcinoma (HCC) tissues promoting HCC cell proliferation and migration ( Cui et al, 2021 ; Yu et al, 2022 ). Thus, the obtained insights into the Spb4 function for ribosome biogenesis could be of relevance for medical studies and treatment of such cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies reported that the human Spb4 homolog DDX55 is strongly upregulated in various lung cancers and hepatocellular carcinoma (HCC) tissues promoting HCC cell proliferation and migration ( Cui et al, 2021 ; Yu et al, 2022 ). Thus, the obtained insights into the Spb4 function for ribosome biogenesis could be of relevance for medical studies and treatment of such cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Oxeiptosis is a specific cellular response to ROS generated by oxidative stress with the potential to induce In this study, the enrichment analysis of biological functions and signaling pathways, the results seem to indicate that OCGs are closely related to both cell proliferation and death, including biological processes such as chromosome structure, mitotic processes, and cell cycle. We noticed that OCGs contain members of several gene families participate in many malignancy-related biological processes, including T-complexpolypeptide1 family, [24,25] Dead-box family [26][27][28][29] and heterogeneous nuclear ribonucleoprotein (hnRNPs) family. hnRNPs is a class of RNA-binding proteins that acts synergistically with the dead-box family in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…TMPRSS2-enriched exosomes were found to suppress the packaging of pro-tumoral nidogen into exosomes and inhibit proliferation and migration of immortalized hepatic cell ( 12 ). In addition, various molecules, including DEAD-box helicase 55 (DDX55), CPE, miR-3129, LINC00161, clathrin light chain A (CTLA), and miR-25, were found to be enriched in cancer-derived exosomes and induce cell proliferation ( 10 , 19 , 21 24 ). Signaling alterations upon sEV treatment primarily involved EMT markers, Wnt/β-catenin signaling, and cell cycle pathways ( 19 , 21 , 23 ).…”
Section: Sevs Derived From Hcc Cancer Cells and Cancer Stemnessmentioning
confidence: 99%
“…In addition, various molecules, including DEAD-box helicase 55 (DDX55), CPE, miR-3129, LINC00161, clathrin light chain A (CTLA), and miR-25, were found to be enriched in cancer-derived exosomes and induce cell proliferation ( 10 , 19 , 21 24 ). Signaling alterations upon sEV treatment primarily involved EMT markers, Wnt/β-catenin signaling, and cell cycle pathways ( 19 , 21 , 23 ). These findings suggest potential mechanisms behind the crosstalk between drug resistance pathways and proliferation signaling via sEVs in HCC.…”
Section: Sevs Derived From Hcc Cancer Cells and Cancer Stemnessmentioning
confidence: 99%